Imaging of Illness in Vanguard Book of Sexual and HIV/AIDS Awareness - Onuoha, Onyekachi Peter (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Literature performs the function of imagining health through imaging of illness and its challenges in African society. The domestication of the digital technology is re-enacting the community narrative in respect to health by virtue of persons coming together to imagine HIV/AIDS within titled anthology specifically for that pandemic. This they do within e-chapbook and through mixtures of genres within a titled anthology. Chapbooks seem to replace print anthologies as a result of its accessibility on the digital space. This paper through the application of the theory of historicism observes that art provides a nexus between health and well being in literature. It observes that Digital anthologies provide a fertile ground for thematic imaging of individual responses to sexual health. This paper illustrates how each writer in Vanguard Book of Sexual and HIV/AIDS Awareness imagines HIV/AIDS and how personas react to it.